Propagation Effects of THz Waves in InAs-Based Heterostructures - Irfan, Muhammad; Yim, Jong-Hyuk; Kim, Dongju; Jang, Jae-Hyung; Song, Jin-Dong; Jho, Young-Dahl (AMER SCIENTIFIC PUBLISHERS, 2014)
We have investigated THz radiation characteristics along different directions, either reflective or along lateral by using InAs-based heterostructures. Firstly, we demonstrate the phase shift with InAs layer thickness, revealing the change of dominant THz wave generation mechanism along both directions. Along the lateral direction, the time-domain signals in thin InAs epilayers showed an abrupt phase and amplitude change at certain time delays which suggest the interference between two rays at the photoconductive switch. This behavior was further substantiated by the multiple cavity modes in Fourier-transformed spectra and by the amplitude variation with excitation spot displacement.
Keywords: TERAHERTZ EMISSION; PHASE; BEAMS